ANALISIS KAIDAH FIQIH TERHADAP REKONSTRUKSI IHDAD BAGI ISTRI YANG BERKARIR DALAM DINAMIKA PERUBAHAN - Yuanda Arlinza, Lola; Duski; Ramelan, Rafida (Program Studi Hukum Keluarga Islam, 2025)
Women who are in a period of progress are mostly women who devote all their energy and thought power to pursue a career to realize their goals and hopes. Women who are married and hold the title of wife also have the right to improve their competence as career women. Wives who have a career and are left to die by their husbands still have to undergo Ihdad. This study aims to examine and analyze the concept of Ihdad for career wives in Islamic law and factors that influence the construction of ihdad for career wives in social change. The type of research used is a literature study (library research) with normative juridical research methods. The results of this study indicate that the concept of Ihdad for career wives in Islam is not absolutely limited to 4 months and 10 days, but can be adjusted to the conditions and roles of these women. While the factors that influence the construction of Ihdad for career wives in social change are economic demands, the competence of women and the times.